2005
DOI: 10.1007/s10108-004-0087-1
|View full text |Cite
|
Sign up to set email alerts
|

Firm-provided training and temporary contracts

Abstract: This paper analyses the relationship between workers’ type of contract and the probability of receiving firm-provided training. In particular, we raise the following question: do workers with temporary contracts face the same probability of receiving training as workers with permanent contracts, once we account for the fact that both types of workers have different probabilities of being employed in a firm providing training? The results from our empirical analysis using data from the Spanish labour market sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 14 publications
6
52
0
11
Order By: Relevance
“…Employing household data, Forrier and Sels (2003) find that Belgian permanent employees are more likely to receive employer-funded training than temporary employees. Similar findings are reported for Spain (Albert et al, 2005;Cabrales et al, 2014) and Germany (Sauermann, 2006). These results are indirectly confirmed by another strand of literature that focuses on the (negative) impact of temporary employment on labour productivity (Dolado and Stucchi, 2008).…”
Section: Training Investments and Non-standard Workers In The Human Csupporting
confidence: 83%
“…Employing household data, Forrier and Sels (2003) find that Belgian permanent employees are more likely to receive employer-funded training than temporary employees. Similar findings are reported for Spain (Albert et al, 2005;Cabrales et al, 2014) and Germany (Sauermann, 2006). These results are indirectly confirmed by another strand of literature that focuses on the (negative) impact of temporary employment on labour productivity (Dolado and Stucchi, 2008).…”
Section: Training Investments and Non-standard Workers In The Human Csupporting
confidence: 83%
“…Moreover, ndings of Shire et al (2009) suggest that rms o ering further training tend to make use of long term contracts rather than temporary employment. The same is reported by Albert et al (2005). They nd that rms, that do not provide vocational training, have higher shares of temporary worker compared to rms o ering further training.…”
Section: Temporary Employment and Human Capitalsupporting
confidence: 67%
“…Several studies show that training participation of workers with temporary contracts is significantly lower than that of workers with permanent contracts (e.g., Booth et al 2002;Forrier and Sels 2003;Almeida-Santos and Mumford 2004;Albert et al 2005). Booth et al (2002) found that, in the UK, work-related training is 12% lower for male employees on fixed-term contracts and 20% lower for those on seasonal-casual contracts compared to male employees with a permanent contract.…”
Section: Prior Researchmentioning
confidence: 99%
“…While most studies in the field compare temporary workers to permanent workers (Booth et al 2002), we are able to distinguish between four different kinds of contract arrangements: permanent contracts, temporary contracts, temporary work agency contracts, and on-call contracts. Moreover, we are able to distinguish between employer-funded training and self-funded training, whereas most studies only focus on employer-funded training (Albert et al 2005). This enables us to analyze whether flexworkers could compensate a lack of employerfunded training by their own investments in training.…”
mentioning
confidence: 99%